Donor–acceptor structure of a coordination polymer with long-lived room temperature phosphorescence and angle-dependent polarized emission. Issue 17 (16th April 2021) - Qin, Wen-Jing; Zhang, Ji-Rui; Tian, Xu-Ke; Yang, Xiao-Gang; Guo, Yu-Ming
Abstract : The formation of a donor–acceptor structure in a coordination polymer results in a long room temperature phosphorescence lifetime (40.22 ms) three orders of magnitude higher than that of pristine phosphor. Abstract : A new strategy to achieve long-lived room temperature phosphorescence performance has been developed via the formation of a donor–acceptor structure in a coordination polymer, which features a lifetime (40.22 ms) three orders of magnitude higher than that of pristine phosphor. It also shows remarkable angle-dependent polarized emission.